PENGENALAN SISTEM AGRIVOLTAIC SEBAGAI TEKNOLOGI PERTANIAN MODERN PADA PETANI SAYURAN DI GANDUS - Yurni Oktarina; Tresna Dewi; Sri Rezki Artini; Siproni Umar (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
The goal of the 2022 Leading Applied Community Service (PKM) program in the Gandus-Palembang sub-district is to help farmers (partners) by providing and applying appropriate technology, specifically solar cell technology as renewable energy, so that farmers (partners) can recognize and use solar energy as an alternative energy in agriculture (agrivoltaic). In this activity, an automatic plant watering system based on solar energy was developed and distributed directly to farmers through socialization in the form of lectures and demonstrations or the practice of making and maintaining solar cell modules. Farmers greatly appreciate this activity and hope that it will be repeated in the future.